Analisis Faktor Penyebab dan Pertanggungjawaban Kecelakaan Truk di Kawasan Perkotaan (Studi Kasus Kecelakaan Truk Ugal-ugalan di Cipondoh) - Sugiarto, Ivan Richard; Hartono, Ernita Dewy; Adhinugraha, Ahmad Shiddiq; Andryawan (Universitas Pahlawan Tuanku Tambusai, 2024)
Transportation tools such as trucks that play an important role in the distribution of goods, but trucks are often the cause of accidents in urban areas. One of the cases that occurred recently was a truck accident in Cipondoh, Tangerang. This study identifies the main causes of accidents and examines the legal responsibility of the parties involved. This study aims to provide an appeal to improve traffic safety and prevent similar incidents from happening again. The research method used is normative juridical with primary and secondary legal sources including a case study of the Case Study of Reckless Truck Accidents in Cipondoh. Library research is a technique used to obtain data in terms of techniques in data collection. The results of the study show that accidents often occur due to driver negligence, as well as in the case of a truck accident in Cipondoh, so strict action and socialization are needed about anticipating accidents to the public.